ASSESSMENT OF THE DUAL TRAINING ITINERARY IN THE DEGREE IN BUSINESS ADMINISTRATION AND MANAGEMENT - José María Beraza Garmendia; Itziar Azkue Irigoyen; Francisco Javier Villalba Merlo (Journal of Management and Business Education, 2021)
This paper shows the steps followed in the implementation of the “Dual Training Itinerary: University-Company” in the Degree in Business Administration and Management - Section of Gipuzkoa, UPV/EHU, the main results obtained by the first promotion and the assessment made by students, company instructors and participating teaching staff. To this end, an e-mailed questionnaire was used to collect information from the different agents who participated in the first promotion of this Dual Itinerary, as well as a focus group in the form of a ”World Café” in which these agents participated. The general assessment of the three main agents involved is very positive. In particular, students consider that the dual training has been adequate to develop the skills of the Degree in Business Administration and Management and they have met the expectations they had before starting it. In addition, the instructors of the companies have shown interest in participating again and they would recommend this modality to other companies.